Streaming flows in differentially heated square porous cavity under sinusoidal g-jitter - Ghosh P.; Ghosh M.K. (My University, 2025)
Transient transport phenomenon in a square porous cavity under sinusoidal g-jitter has been solved numerically. Sinusoidal g-jitter introduces a true periodic behavior to the average Nusselt number. Pulsating wave from hot and cold side travels to-wards the center and almost in the center of the cavity the two waves engage in constructive/destructive interference leading to the formation of stationary wave. Sinusoidal g-jitter creates the streaming flows inside the porous cavity and time-dependent rolls have been observed inside the cavity due to differences in thermal diffusivities among solid matrix, wall and the fluid. © 2008 Elsevier Masson SAS. All rights reserved.